THE STATUS OF SCHOOL LIBRARY AUTOMATION IN MALAYSIAN CHINESE SECONDARY SCHOOLS: A NATIONAL SURVEY - Swee, Tee Lay; Abdullah, Abrizah (Malaysian Journal of Library and Information Science, 2005)
This article presents the findings of a survey undertaken to determine the current status of library automation in Malaysian Chinese Secondary Schools (MCSSs), which comprise the Independent Chinese Secondary Schools (ICSS) and the National-type Secondary School (NTSS). Questionnaire was mailed to all school libraries from 60 ICSS and 76 NTSS. A total of 89 respondents (65.4%) returned the questionnaires, of which 56 (73.7%) were from the NTSS and 33 (55.0%) from ICSS. Follow-up interviews conducted over the telephone were also carried out to gather supporting information. The study showed that the MCSS libraries started to automate during the 1990s and have been actively involved in library automation projects since 2000. A total of 43.8% school libraries (39.3% NTSS and 51.5% ICSS) have automated their library functions. The study found that circulation is the function mostly automated by libraries, followed by cataloguing. Turnkey system is the choice for most automated NTSS libraries, whereas ICSS libraries opt for systems developed in-house. A total of fifty (56.2%) libraries are not automated, however 39 of them (78.0%) plan to do so in the near future. Small size libraries and libraries with no budget for automation do not plan to automate their libraries function. Management decision is the most important factor in conducting library information work. The research has also identified important factors in determining the systems used, and areas need for future planning initiatives in implementing library automation.